1998
DOI: 10.1177/135910539800300403
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Motives and Stages of Change

Abstract: The aim was to examine how exercise motives differ across stages of change. British government employees completed questionnaires measuring exercise motives and exercise stage of change at baseline (N = 425) and at 3-month follow-up (247 of the original sample). Discriminant analysis was used to determine whether exercise motives (and age and gender) could collectively discriminate between baseline stages of change; and whether exercise motives could discriminate between those who stayed inactive, stayed activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
122
3
9

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 20 publications
6
122
3
9
Order By: Relevance
“…In the context of exercise adoption, the Transtheoretical Model argues that individuals move through five stages of behavioural change, starting from being physically inactive and ending up as regular exercisers. Ingledew et al (1998) found that extrinsic, especially body-related, motives were more important in the early stages of behavioural change, whereas enjoyment (an intrinsic motive) was important for progression to regular exercise patterns. However, Ingledew et al (1998) used a descriptive questionnaire which measures motives for exercise (some of which can be high or low in self-determination depending on how they are operationalized), but not the underlying motivational regulations that underpin exercise behaviour.…”
Section: Sdt and Exercise-related Behavioursmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of exercise adoption, the Transtheoretical Model argues that individuals move through five stages of behavioural change, starting from being physically inactive and ending up as regular exercisers. Ingledew et al (1998) found that extrinsic, especially body-related, motives were more important in the early stages of behavioural change, whereas enjoyment (an intrinsic motive) was important for progression to regular exercise patterns. However, Ingledew et al (1998) used a descriptive questionnaire which measures motives for exercise (some of which can be high or low in self-determination depending on how they are operationalized), but not the underlying motivational regulations that underpin exercise behaviour.…”
Section: Sdt and Exercise-related Behavioursmentioning
confidence: 99%
“…Ingledew et al (1998) found that extrinsic, especially body-related, motives were more important in the early stages of behavioural change, whereas enjoyment (an intrinsic motive) was important for progression to regular exercise patterns. However, Ingledew et al (1998) used a descriptive questionnaire which measures motives for exercise (some of which can be high or low in self-determination depending on how they are operationalized), but not the underlying motivational regulations that underpin exercise behaviour. In contrast, assessed the variations in four motivational regulations (intrinsic motivation, identified, introjected and external regulation) across the different stages of change.…”
Section: Sdt and Exercise-related Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mainstream sport and exercise psychology research, the most common motives/reasons utilised in questionnaires and tests are these: exercising for interest/enjoyment, competence, fitness, body-related motives such as weight control, improving body tone and overall physical attractiveness, health/health pressures, ill-health avoidance, stress management improving mood, affiliation, challenge, competition, revitalisation, and social recognition (Markland & Hardy, 1993;Silberstein, Striegel-Moore, Timko, & Rodin 1988). These various motives/reasons for exercise seem to have different importance at different stages of exercise, with motives concerning appearance and weight-control being more pertinent in the initiation-stage, and enjoyment and revitalisation being more important for progression to the maintenance of regular exercise (Ingledew, Markland, & Medley, 1998). …”
Section: Motives For Exercisingmentioning
confidence: 99%